More-than-human in the garden: Living with Homo hortensis - Schwarz Astrid (Cultural Science, 2022)
In contrast to Homo faber, Homo hortensis does not side with technical production. He is dependent on dealing with inhomogeneous, ‘impure’ ensembles and can thus offer an interesting approach of acting in the age of the Anthropocene. Dealing with the interweaving of the natural and the artificial, craftsmanship and mechanization, local traditional and scientific knowledge is inherent in gardening practice and has been this way for centuries. Homo hortensis is a genuinely technoscientific person for whom the garden is an ecotechnical product of co-produced knowledge and material. The garden is a counterpart and demands attentive perception, and in this sense offers a model for a convivial mode to live with many others. The garden demands a sense of situatedness and requires the gardener to constantly position himself in his gardening work. This is where Homo hortensis differs dramatically from other forms of horticultural management, for example in geoengineering, industrial agriculture and many sustainability industries.